Barakah Conversion Mechanism in Islamic Market Transactions: An Economic Anthropology Perspective on Value and Satisfaction - Sukamto; Nur Kholis; Siti Musfiqoh (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2026)
Islamic market transactions integrate economic, ethical, and spiritual dimensions that are not fully captured by conventional models of value and satisfaction. This study examines how barakah (divine blessing) shapes value and satisfaction in Islamic market transactions from an economic anthropology perspective. Existing studies on halal marketing and Islamic consumer behavior have largely treated religiosity and ethical attributes as predictors of trust or loyalty, while the lived mechanism through which spiritual values become embedded in market exchange remains underexplored. Using ethnography, data were collected through participant observation and in-depth interviews with Muslim traders and consumers in the Ampel religious tourism district of Surabaya, Indonesia. The findings show that barakah operates as a moral-economic mechanism linking spiritual commitment to trust, satisfaction, business continuity, and redistributive consumption. Traders enact barakah through honesty, transparency, and halal integrity, while consumers interpret these practices as signs of religious accountability, strengthening satisfaction and repeat patronage. The study also finds that taṣarruf (purposeful spending) connects functional consumption with spiritual intention and informal redistribution. This study contributes to Islamic economics by positioning barakah as a lived market mechanism that strengthens ethical authenticity, consumer trust, and long-term resilience in Islamic business practice.